Identification of Intestine Parasite Worms Eggs in Feces Proboscis Monkey (Nasalis larvatus) - Rahman, Fiqita Giulleta Irtifannisa; Nurliani, Anni; Rezeki, Amalia; Rusmiati, R (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The proboscis monkey (Nasalis larvatus) is one of the endemic primates on the island of Borneo which is protected in Indonesia. Rehabilitation efforts are important to prevent extinction of the proboscis monkey. Parasitic diseases are diseases that often infect primates in rehabilitation centers. Examination feces is one way to diagnose the presence of parasitic worms in the animal's body. This study aims to identify and know Prevalence of types of parasitic worms found in the feces of proboscis monkeys at the Bekantan Rescue Center Sahabat Bekantan Foundation (SBI). Sampling of proboscis monkey feces was carried out for 20 days on three proboscis monkeys at SBI. Identification of endoparasites is carried out in the Parasitology Laboratory, Banjarbaru Veterinary Center, South Kalimantan, using the Whitlock sedimentation method. The results of this study indicate that there are types of worms Trichuris trichiura, Trichostrongylus sp. and Oesophagostomum sp. found in proboscis monkey feces samples. The highest prevalence was found in the type of worm Trichuris trichiura which was found in Mimin's proboscis monkey, which was 35%.